Transcriptome-based identification of key actin-binding proteins associated with high metastatic potential in breast cancer - Müller, Christian; Oliveira-Ferrer, Leticia; Müller, Volkmar; Schmalfeldt, Barbara; Windhorst, Sabine (Frontiers in Molecular Biosciences, 2024)
Actin binding proteins (ABPs) are essential for the regulation of morphological plasticity required for tumor cells to metastasize. Aim of this study was to perform an unbiased bioinformatic approach to identify the key ABPs significantly associated with the metastatic potential of breast cancer cells.Methods: Microarray data from 181 primary breast cancer samples from our hospital were employed, and all genes belonging to the Gene Ontology term actin cytoskeleton organization obtained from QuickGO. Association with metastasis-free survival probability was tested using Cox proportional hazards regression, and pairwise coexpression by Pearson correlations. Differential expression between different subgroups was analyzed by Wilcoxon tests for dichotomous traits, and Kruskal-Wallis tests for categorical traits. Validation was performed in four publicly available breast cancer datasets.Results: ARHGAP25 was significantly associated with a low, and CFL1, TMSB15A and ACTL8 with a high metastatic potential. A significantly higher expression of CFL1, TMSB15A and ACTL8 mRNA was found in the more aggressive Her2 positive and triple negative subtypes as well as in ER-negative samples. Also, these genes were co-expressed in the same tumors. However, only mRNA levels of CFL1 were increased in pN1 compared to pN0 patients. External validation revealed that CFL1 and TMSB15A had significant associations with consistent hazard ratios in two breast cancer cohorts, and among these CFL1 exhibited the highest Hazard ratios.showed the strongest correlation with the metastatic potential of breast tumors. Thus, targeted inhibition of CFL1 might be a promising approach to treat malignant breast cancer cells.